2019
DOI: 10.2528/pierm19052202
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Dielectric Properties of Cow's Raw Milk Under Vat Pasteurization

Abstract: An efficient microwave milk pasteurization system requires a rigorous temperature dependent dielectric model of the milk, since the performance of milk pasteurization strongly depends on its dielectric properties. This paper describes the dielectric modelling of cow's raw milk during batch (Vat) pasteurization which covers the frequencies from 0.2 GHz to 6GHz. An open-ended coaxial sensor is used for the measurements of dielectric constant, loss factor, and ionic conductivity at temperature range of 25 • C to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Hence, there is a significant risk of microbial contaminants from the animal to the pastures and the equipment, to the effect that the consumption of raw milk may cause food-borne infections. Pasteurization of milk is thus essential to guarantee its quality and to extend its shelf-life ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a significant risk of microbial contaminants from the animal to the pastures and the equipment, to the effect that the consumption of raw milk may cause food-borne infections. Pasteurization of milk is thus essential to guarantee its quality and to extend its shelf-life ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…This method has led to the amount of rare particles present in food such as ampicillin (Lee et al., 2020). The results also determined that among nutrients, protein has the greatest effect on the dielectric properties of milk (Zhu et al., 2014), but these results do not have the same answer at all frequencies because in (Abdullah et al., 2019) has been showed that at different frequency bands these results may change and many factors are involved in this issue. The shape of the container is one of the factors that effect on the permittivity, so for comparison between different materials, it needs to be used from the same containers (Dag et al., 2019; Leite et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Interestingly, in the last few decades, RF sensing has gained the interest of several researchers to perform a qualitative analysis of milk samples, including identification of solute level in the virgin solvent. [13][14][15] However, most of these techniques, which employ RF sensing methods, have mainly engaged the commercially available dielectric probe kit, which is quite costly and nonplanar, limiting their practical applicability. 13,14 Usually, the RF sensing mechanism primarily relies on the processing of either broadband S-parameters or narrowband S-parameters, generated using non-resonant and resonant RF sensor structures, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Usually, the RF sensing mechanism primarily relies on the processing of either broadband S-parameters or narrowband S-parameters, generated using non-resonant and resonant RF sensor structures, respectively. [7][8][9][13][14][15] Out of non-resonant and resonant RF sensors, the resonant RF sensors are relatively more accurate and sensitive and can suitably be employed for milk adulteration testing. 16 It is also important to note here that the resonant RF sensor's implementation can usually be categorized into two sub-groups, that is, non-planner and planner resonant RF sensors.…”
Section: Introductionmentioning
confidence: 99%